2012
DOI: 10.5424/sjar/2012104-2813
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Citrus tristeza virus in nursery blocks of Citrus macrophylla and evaluation of control measures

Abstract: The control of Citrus tristeza virus (CTV), the causal agent of tristeza disease, is essential to guarantee a productive citrus industry. The specific features of a nursery block make the control of the natural spread of viruses transmitted by vectors more difficult. Thus, the knowledge of the epidemiology of CTV in nursery blocks is basic to the design control strategies of the disease. Two experimental nursery plots of alemow (Citrus macrophylla) were planted in open field in Moncada (Valencia, Spain) (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…These methods include the observation of established colonies, suction, water and sticky fishing-line traps as well as the sticky plant or shoot method (Cambra et al, 2006). The sticky shoot method, which uses glue-covered bait leaves, shoots or the entire plant, has been extensively used to determine the arthropod species that visit crops and monitor aphid species in adult trees (Cambra et al, 2000;Marroquín et al, 2004;Vidal et al, 2012). This method is the most efficient for estimating the numbers of insects landing on the plants (Hermoso de Mendoza et al, 1998).…”
Section: Hosts and Monitoring Sitesmentioning
confidence: 99%
“…These methods include the observation of established colonies, suction, water and sticky fishing-line traps as well as the sticky plant or shoot method (Cambra et al, 2006). The sticky shoot method, which uses glue-covered bait leaves, shoots or the entire plant, has been extensively used to determine the arthropod species that visit crops and monitor aphid species in adult trees (Cambra et al, 2000;Marroquín et al, 2004;Vidal et al, 2012). This method is the most efficient for estimating the numbers of insects landing on the plants (Hermoso de Mendoza et al, 1998).…”
Section: Hosts and Monitoring Sitesmentioning
confidence: 99%
“…Lee and Bar‐joseph () and Vidal et al . () reported that tristeza disease is easily dispersed in the Mediterranean area by A. gossypii and other aphid species, such as A. spiraecola . Furthermore, it has been estimated that in the Valencian citriculture (Spain), the CTV infection by only aphid transmission reaches 75%–95% of the infected trees (Cambra & Gorris, ).…”
Section: Discussionmentioning
confidence: 99%
“…He specified the joint likelihood function as poisson binomial distribution. Vidal et al (2012) described that CTV incidence and severity increased in older plantations than in younger ones. The spatio-temporal distribution of CTV disease depends upon susceptibility of citrus cultivars, infectivity of virus isolates and population dynamics of vector (Moreno et al, 2008).…”
Section: Ctv Disease Severity In Mosambi Orchardsmentioning
confidence: 99%